Penerapan Terapi Pijat Kaki pada Pasien Hipertensi di Panti Jompo Palembang - Nengah Aditya; Sri Indaryati; Novita Elisabeth Daeli (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Complications such as stroke, heart attack, kidney failure, and heart failure can arise as a result of hypertension as a long-standing disease. Foot massage can help lower blood pressure and dilate blood vessels, reducing complications of hypertension. The aim of EBPN is to analyze the application of Evidence Based Practice Nursing (EBPN) foot massage therapy in hypertensive patients. The method for implementing EBPN through case studies uses a descriptive method with a One Group Pretest-Posttest approach to foot massage therapy (3 times for 15 minutes in 3 consecutive days) to reduce blood pressure. The sample consisted of 1 female respondent and 2 male respondents. The tensimeter and observation sheet are the measuring tools used. EBPN results: All 3 (100%) respondents had suffered from hypertension for > 5 years. There was a change in blood pressure before and after the intervention with the results: respondent 1 BP 139/85 mmHg to 130/80 mmHg, respondent 2 BP 139/88 mmHg to BP 130/82 mmHg, and respondent 3 BP 147/97 mmHg to BP 138/89 mmHg. The average decrease in systolic blood pressure in the 3 respondents was 8.5 mmHg, while diastole decreased by an average of 5.8 mmHg. The suggestion for hypertension sufferers is that hospital staff can offer foot massage as a method to lower blood pressure to patients suffering from hypertension.